KARAKTERISASI MIKRO DAN NANOSELULOSA HASIL EKSTRAKSI DARI SERAT SISAL DAN KENAF - , Purwanto; , Prof. Dr. Achmad Djunaedi, MUP., ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In general, this study aims to increase the facility service in the college. In specific, it aims to evaluate the utilization of lecture room and studio in the Department of Architecture and Planning, Faculty of Engineering, Gadjah Mada University. This study used evaluation research where this research focused on an activity in certain unit. That activity could take form of program, process, or work